STATUS MENARCHE BERDASARKAN IDEKS MASSA TUBUH DAN LINGKAR LENGAN ATAS DI SMPN 37 PALEMBANG - Atma Deviliawati (Masker Medika, 2022)
Introduction: About 1 billion people or every 1 in 6 of the world's population are teenagers. In America the median age of menarche fell by 0.9 years for women born before 1920 compared with women born before 1980-1984, the average age at menarche for women born in 1920 was 13.3 years old and for women born 1980-1984 is 12.4 years old. In Indonesia, the number of adolescents and young people is growing rapidly. Generally, teenagers experience menarche at the age of 12 to 16. This period will change behavior from several aspects, such as psychology and others. Methods: This type of research is an observational survey to find out the description of menarche status based on the Body Mass Index and Upper Arm Circumference which was conducted at SMPN 37 Palembang in 2019. The research sample was 133 seventh grade students obtained using the total sampling technique. Univariate analysis was used to determine the distribution of respondents' characteristics. Results: Students who experienced menarche were 66 people (49.6%), the early category was 42 people (63.6%), the most experienced menarche at the age of 11 years with 37 people (56.1%), and the most at least 9 years old with 1 person (1.5%). while the age of 10 years with 4 people (6.1%), age 12 years with 20 people (30.3%) and age 13 years with 4 people (6%). Body Mass Index of 66 people who experienced menarche was 28 people in thin body (42.4%), 33 people in normal body (50%) and 5 people in fat body (7.6%). Upper arm circumference based on menarche status, 30 skinny people (45.5%) and 36 people with normal body (54.5%). Discussion: Adolescent girls at puberty will experience their first menstruation or menarche, menarche can occur earlier or later depending on body condition.